INTERAÇÃO HOMEM E MÁQUINA: A CONSTRUÇÃO DOS PROCESSOS DE COMUNICAÇÃO EM INTELIGÊNCIA ARTIFICIAL - GABATELLI, LUIS OCTAVIO (2019)
The discussion about communication interaction between men and machines was expanded in the 21ST century by means of artificial intelligence (AI) software. In this sense, through an exploratory methodology, this research seeks to understand how communicational processes occur in intelligent machines. Following this perspective, we first discuss in this study a set of theories of Communication, in particular the Mathematics and the School of Palo Alto, in the face of different ways of thinking about information and communication in intelligent machines. In a second moment, we discuss a repertoire of a more technical nature, conceptualizing the history of artificial intelligence and the technologies of machine learning and natural language processing (PLN). Aiming to investigate the sublayers that involve the practice of machine communication, we complemented the study with the analysis of an artificial intelligence product, the Watson Assistant from IBM company. As an analysis criterion, prioritize the selection of the main tools that the system offers for chatbots, communicate and interact with humans. In addition, highlighting how to purchase other applications can influence machine communication if integrated into Watson Assistant. Finally, for more consistent answers to the problem raised, confronting Watson's analysis with a set of assumptions surrounding the Mathematical Theory of Communication and the Palo Alto School.